Binding of Hepatitis C Virus E2 Glycoprotein to CD81 Does Not Correlate with Species Permissiveness to Infection - Meola, Annalisa (American Society for Microbiology, 2000)
Hepatitis C virus (HCV) glycoprotein E2 binds to human cells by interacting with the CD81 molecule, which has been proposed to be the viral receptor. A correlation between binding to CD81 and species permissiveness to HCV infection has also been reported. We have determined the sequence of CD81 from the tamarin, a primate species known to be refractory to HCV infection. Tamarin CD81 (t-CD81) differs from the human molecule at 5 amino acid positions (155, 163, 169, 180, and 196) within the large extracellular loop (LEL), where the binding site for E2 has been located. Soluble recombinant forms of human CD81 (h-CD81), t-CD81, and African green monkey CD81 (agm-CD81) LEL molecules were analyzed by enzyme-linked immunosorbent assay for binding to E2 glycoprotein. Both h-CD81 and t-CD81 molecules were able to bind E2. Competition experiments showed that the two receptors cross-compete and that the t-CD81 binds with stronger affinity than the human molecule. Recently, h-CD81 residue 186 has been characterized as the critical residue involved in the interaction with E2. Recombinant CD81 mutant proteins were expressed to test whether human and tamarin receptors interacted with E2 in a comparable manner. Mutation of residue 186 (F186L) dramatically reduced the binding capability of t-CD81, a result that has already been demonstrated for the human receptor, whereas the opposite mutation (L186F) in agm-CD81 resulted in a neat gain of binding activity. Finally, the in vitro data were confirmed by detection of E2 binding to cotton-top tamarin (Saguinus oedipus) cell line B95-8 expressing endogenous CD81. These results indicate that the binding of E2 to CD81 is not predictive of an infection-producing interaction between HCV and host cells.